PRODUKTIVITAS INDUSTRI GULA SINGKONG “MANES” - Wagiyo Wagiyo; Arohman Arohman; Dhel Juni Pasa; Jundi Abdul Aziz (Universitas Muhammadiyah Pringsewu, 2022)
“Manes” Cassava Sugar is a home industry that produces sugar produced from cassava which is its main ingredient. Cassava sugar has the specialty of being 2 times as sweet as sugar in general, cassava sugar is good for consumption by diabetics because it is 100% natural and has low glucose. The implementation uses the direct visit method to the location on August 2, 2022 at the “Manes” Cassava Sugar MSME with the address Jln. Psr. Sweet No 99, Kepiring, Punggelan, Banjarnegara Regency, Central Java, The production of liquid cassava sugar reaches 20 tons per month. Brands circulating in both traditional and online markets include